Development of a Self-Powered Environmental Sensing Platform for Smart City Applications: A Case Study on Weather Stations with LoRaWAN Integration - Bindu Jamwal (Research Scholar), Dr. Rajendra Singh (HoD) (Journal of Computational Analysis and Applications (JoCAAA), 2024)
This paper has proposed the design of a self-powered environmental sensing platform thatcan be used as part of Smart City solutions, in this case weather stations with LoRaWANcommunication technology. The real-time monitoring of the environment has been on the rise as cities are becoming more and more problematic